COMPARATIVE STUDY OF THE CRIMINAL REGULATION OF HOMOSEXUAL ACTS IN INDONESIAN AND MALAYSIAN LAW - Tsabitha, Calista Marsha; Rosmaya, Ina (jfpublisher, 2025)
Homosexuality is often debated in the world community. Many countries are against homosexuals. However, some are also in favor of these social deviations. Indonesian society considers homosexuality deviant and violates religious rules. Likewise in Malaysia, which has a background of not legalizing same-sex marriage and instead criminalizing it. This research aims to compare the legal regulation of homosexuality in the perspective of Indonesian criminal law and Malaysian criminal law. As well as to find out matters related to the regulation of homosexual criminal law in Indonesia and Malaysia. The method used in this research is normative research, namely by using various secondary data including laws, court decisions and legal theories. This research found various differences and similarities in regulating homosexuals from the perspective of the legal regulations of the two countries. Indonesia has legal rules for homosexual offenders who intentionally commit same- sex sexual abuse by minors in Article 292 of the Criminal Code. In particular, homosexual acts have no binding legal rules and are still a legal vacuum. Whereas Malaysia considers homosexuality a sexual deviation that needs to be strictly punished according to the state 377AB Kanun Keseksaan or Malaysia Code Penal and Sharia law. In terms of legal sanctions, Indonesia has similarities, namely imprisonment, fines, and whipping. Whipping for all Muslims in Malaysia who commit homosexual crimes. Meanwhile, flogging in Indonesia is specifically stipulated in the Aceh region which violates the rules, one of which is homosexuality or liwath.